Strategi Pengembangan Kompetensi SDM Pengrajin Ulos untuk Meningkatkan Daya Saing Produk Lokal (Tenun Batak Melayu) Rehani di Desa Sidorejo Hilir Kecamatan Medan Tembung - Pribadi, Teddy; Marbun, Patar; Banjarnahor, Marali (Universitas Pahlawan Tuanku Tambusai, 2025)
Improving human resource competency is a strategic long-term investment and has broad dimensions in all aspects. Therefore, integrated steps and willingness are needed from the leadership as policy makers and the workforce who act as development subjects. Improving the competency of Human Resources in the form of mental skills, soft skills, hard skills, social skills, has become an unavoidable demand for organizations in the new normal era to support the performance of the workforce and management. The purpose of this community service is to socialize the Development of Human Resource Competence to Increase the Competitiveness of Rehani Local Products (Malay Batak Weaving) Rehani as a business actor in Sidorejo Hilir Village, Medan Tembung District. The method used in this service uses the ABCD method, which provides assistance in training Competency Development to business actors. The results of the implementation of this activity are that the assistance has had a positive impact on the community and MSME actors in the form of increasing the ability and quality of employees with the aim of achieving better performance for each employee and the organization as a whole. In this training, the role of the assistant is very important in providing support, guidance, and motivation for the community. Behavioral engineering contains the implied meaning that behavior can actually be changed and improved, from one state to another, better state.